Developing trust and commitment among non-profit companies: the case of the food bank in Cali, Colombia (2010)
The most recent trends and research findings clearly show that the markets have experienced a significant change. Stakeholders in the market have shifted their orientation. They are now more focused on relationship marketing than on transactional marketing. Given the fact that relationship marketing is tightly linked with long-term time horizons, trust between the parties plays a very important role. This study analyzes the factors that have an impact on trust among non-profit companies. The researchers follows an empirical approach, focusing on showing the characteristics of and relationships between donors and non- profit companies, and how these relationships affect the trust which develops between the parties. The study was conducted at a non-profit company called “Banco de Alimentos” (food bank) in Cali, Colombia. It involved interviewing 68 donors in total, including companies from different economic sectors (i.e. manufacturing, public sector, financial sector, services, business, and healthcare) as well as individuals.